The Application of Geographic Information System (GIS) in Food Distribution Across Indonesia - Abdus Syakur; Budi Setiawan (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
Food distribution and the food supply chain are major issues in achieving food security in Indonesia. Geographical disparities, poor transportation systems, and social differences in Indonesia cause high complexity challenges in implementing a perfect distribution system that suits Indonesia's characteristics. The objective of this study is to build an application for a food distribution using a Geographic Information System (GIS) that can be implemented in Indonesia. The research method is the SDLC (System Development Life Cycle) approach with a Prototyping Model. The data collected consisted of spatial data in the form of Indonesian maps with the provinces as the mapping unit, and each province has a capital city that acts as a center point for food distribution. Attribute data consisted of province’s profiles, food productivity for each commodity, food supply, food sources and food exports. GIS can visualize all data layers into maps that are easier to analyze. Indonesia consists of 38 provinces spread across many islands, and each has its specific geographic profiles and transportation problems. Building a food distribution application is part of developing a food distribution system that produces a system prototype. The prototyping approach is used to evaluate the results of the GIS design by analyzing the features of food distribution in Indonesia. The result of this study is an application that can be implemented into a food distribution system that can create stable food security in Indonesia for all provinces.